2009
DOI: 10.1007/s10995-009-0529-3
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between Self-Report and Birth Certificate for Gestational Diabetes Mellitus: New York State PRAMS

Abstract: This study examined agreement (concordance or convergent validity) between self-report and birth certificate for gestational diabetes. Study population was 2,854 women who had live births 2-6 months earlier and responded to a questionnaire from the New York State Pregnancy Risk Assessment Monitoring System (PRAMS) survey, 2004-2006. Agreement between self-report and birth certificate was assessed for the study population overall, and for subgroups defined by race, age, education, marital status, number of prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 10 publications
3
43
0
Order By: Relevance
“…A questionnaire was designed based on a review of the maternal recall literature on gestational diabetes, 21 preeclampsia, 22,23 birthweight, [24][25][26] and gestational age at delivery. [26][27][28][29][30][31][32][33][34][35] The questionnaire was piloted among the first 10 patients scheduled on a given day in both a general obstetrics and a maternal fetal medicine practice who agreed to complete the survey.…”
Section: Methodsmentioning
confidence: 99%
“…A questionnaire was designed based on a review of the maternal recall literature on gestational diabetes, 21 preeclampsia, 22,23 birthweight, [24][25][26] and gestational age at delivery. [26][27][28][29][30][31][32][33][34][35] The questionnaire was piloted among the first 10 patients scheduled on a given day in both a general obstetrics and a maternal fetal medicine practice who agreed to complete the survey.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence from the German perinatal statistics -at 3.7 % for the most recent available year -is below the figure provided by the KiGGS, which even for the years 2001 to 2006 led to a value of 5.3 %. Self-reported information can lead to significantly higher values than register-based data, as two studies from the USA have also shown: in these cases, prevalences were 9.0 and 8.7 % for self-reported information, versus 4.8 % in each case for medically validated and centrally-registered diagnoses, equivalent to differences of 4.2 or 3.9 percent points [8,9]. The comparison of the data sources used in this study indicates that the diagnosis of gestational diabetes was obviously not entered into the documentation program by the maternity hospitals in all cases.…”
mentioning
confidence: 94%
“…A recent review of studies evaluating the validity of birth certificates in identifying maternal diabetes reported sensitivities ranging from 47 to 52% for pre-gestational diabetes and 46 to 83% for gestational diabetes when compared to various standards (Devlin et al, 2009). A study of agreement between birth certificates and self-reported data from Pregnancy Risk Assessment Monitoring System respondents observed a lower prevalence of gestational diabetes reported on birth certificates (4.8 vs. 9%), accompanied by a percent agreement of 93.8% but only moderate agreement when chance agreement was taken into consideration (Kappa 5 0.53) (Hosler et al, 2009). …”
Section: Discussionmentioning
confidence: 99%